OPTIMAL THERMAL ANALYSIS OF CORONAVIRUS (COVID-19) TRANSMISSION DURING QUARANTINE DAYS IN PERU - Calderón Ch, J. Alan (2021)
In this research is analyzed COVID-19 transmission by thermodynamic and energy balance between geographic areas and its correlation with possible COVID-19 transmission between 2 persons at least. In order to achieve parameters for medical doctors, as for example the minimal distance among two infected people, who have this virus, there were designed mathematical models that were based in statistical data to get information of COVID-19 propagation as the dependence on temperature of geographic areas, moreover the thermal effect of the minimal distance between two people avoiding COVID-19 infection. With this work, answers are sought to the questions: if it could be possible to find a relation between temperature and virus transmission? Or if it could be possible to get a correlation variable among thermal variables with minimal distance separation (it was described above) for two people? Hence, it is waited answers to these questions owing to be support for medical doctors, who are trying to find solution against COVID-19 propagation. It is worth mentioning that this research can be extended to more complex areas such as street markets, street fair or enclosed marketplaces, where products and services are sold, moreover, not every area has an air conditioning system in Peru. Nevertheless, in this research it is achieved the technique, how to solve this task: to obtain appropriated ventilation parameters as the dependence on the minimal distance that people need to be separated, according to avoid virus transmission between each other. Furthermore, it is suggested some geometrical/material characteristics for air filters and ultraviolet (UV) disinfection at the entrance of the main air duct.